Effect of malnutrition on the pharmacokinetics of cefuroxime axetil in young rats - Iliana González; Angela Sotelo; Helgi Jung (Journal of Pharmacy & Pharmaceutical Sciences, 2008)
Purpose: To determine the pharmacokinetics of cefuroxime axetil in malnourished rats using a diet with a restriction in energy and nutrients (group M), a diet with a low quality protein (group K) and a good quality diet (group C) as a control. Methods. The rats were fed with the corresponding diet during 21 days. After this period a single oral dose of cefuroxime axetil (equivalent to a 2.2 mg dose of cefuroxime) was administered, and plasma samples were taken at 0, 5, 10, 30, 45, 60, 90, 120, 180, 240, 300 and 360 minutes; samples were assayed using an HPLC assay. Biochemical parameters were also measured an a microscopy study of the small intestine was done. After a 21 day period of recovery of the malnourished groups a second pharmacokinetic study was performed using the same sample times as in the first study. Results: In malnourished animals of group K the levels of plasma proteins were low, and showed higher concentrations of fat in the liver. The relative bioavailability of cefuroxime was 78.2% for group M and 64.4% for group K. Groups M and K presented lower values of area under the curve, which means that the amount of antibiotic absorbed was lower than group C. In the second pharmacokinetic study although the animals received a good quality diet, it was observed that the area under the curve of group K was lower, and the relative bioavailability was 54.3%, while group M had similar pharmacokinetic values than control group. Conclusions: The pharmacokinetics of cefuroxime was affected by malnutrition, suggesting that the absorption process via the transporter was modified in the malnourished groups, specially in the group fed with a low quality protein.